The collection of micrometeorites in the Yamato Meteorite Ice Field of Antarctica in 1998 - Yada, Toru; Kojima, Hideyasu (National Institute of Polar Research, 2000)
P(論文) In austral summer season of 1998,we collected micrometeorites at the Meteorite Ice Field around the Yamato Mountains, Antarctica. It was the first attempt to collect micrometeorites at inland bare ice in Antarctica and to use a filter with 10μm openings; it can capture particles that overlap in size with interplanetary dust particles collected in stratosphere. At the inland bare ice of the Antarctic Continent, an ancient flux of extraterrestrial dust is thought to be preserved in contrast with bare ice along the shore of the continent. For collecting micrometeorites from the bare ice, we used a tented sledge equipped with appliances for melting ice and filtering the melted water. We melted ∿ 36 tons of ice and obtained particles containing micrometeorites at 24 points in three areas of the Meteorite Ice Field. departmental bulletin paper